Catalytic Effects of Red Mud and Acidithiobacillus ferrooxidans on Biodissolution of Pyrite. Issue 1 (May 2021) - Lin, Mo; Yang, Baojun; Lin, Hao; Liu, Shitong; Wang, Jun
Abstract: The catalytic effect of red mud on biodissolution of pyrite was studied with Acidithiobacillus ferrooxidans in this study. Dissolution and results showed that red mud could significantly promote pyrite biodissolution. The bacterial group with 4g/L red mud had best dissolution effect. The iron extraction rate in the group was 47.9% higher than the control group. Red mud in sterile group could inhibit pyrite dissolution. The iron extraction rate in the group with 8.0g/L red mud was 75.4% lower than the control group. The biodissolution results indicated that red mud could accelerate pyrite dissolution by promoting electron transfer in biodissolution system and enhancing the growth of A. ferrooxidans .